Immunological differences between monophasic and biphasic synovial sarcoma with implications for immunotherapy - S. J. Luk; M. E. IJsselsteijn; A. Somarakis; I. Acem; I. Briaire de Bruijn; K. Szuhai; J. V. M. G. Bovee; N. F. C. C. de Miranda; J. H. F. Falkenburg; M. H. M. Heemskerk (Cancer Immunology, Immunotherapy)
Abstract Synovial sarcoma is an aggressive soft-tissue cancer that shows limited responses to current immunotherapeutic approaches using immune checkpoint blockade or adoptive cell therapy. To improve immunotherapy for this cancer, understanding how the immune cells in the tumor microenvironment associate with histological subtype, disease progression and current therapies is vital. To evaluate the immune infiltrate in synovial sarcoma in relation to histological subtype, disease progression and in response to cytotoxic treatment, we performed immunodetection of T cells, CD68+ myeloid cells, endothelial cells and keratin on a series of 41 synovial sarcoma patients at various stages of disease. The immune composition of synovial sarcoma was dominated by CD68+ myeloid cells of which a substantial part was of the CD163+ immunosuppressive phenotype, which increased after chemotherapy or radiotherapy. Biphasic synovial sarcomas were more densely infiltrated by both T cells and myeloid cells than monophasic synovial sarcomas. In these tumors, the immune and endothelial cells were mostly located within the stromal like, spindle cell compartment and excluded from the epithelial compartment, greatly resembling the spatial organization of healthy epithelium such as in the colon. Together these data demonstrate that biphasic synovial sarcoma is immunologically different from monophasic synovial sarcoma and might be more susceptible to immunotherapies such as adoptive T-cell therapy. Finally, T-cell infiltration in primary synovial sarcoma was associated with prolonged overall survival of patients which suggests that intratumoral T cells may demonstrate anti-tumor activity.